Surface electromyography data analysis for evaluation of physical exercise habits between athletes and non-athletes during indoor rowing - Grzejszczak, T.; Roksela, A.; Poswiata, A.; Siemianowicz, A.; Kielbon, A.; Mikulski, M. (Sensors, 2024)
In this paper, surface electromyography (sEMG) is used to gather the activation neural signal from muscles during an indoor rowing exercise. The exercise was performed by professional athletes and amateur non-athletes. The data acquisition and processing are described to obtain a set of parameters: number of cycles, average cycle time, cycle time standard deviation, fatigue time, muscle activation time, and muscle energy. These parameters are used to draw conclusions on common non-athletes` mistakes during exercise for better training advice and a way of statistically distinguishing an athlete from a non-athlete.